Implementasi Model Pembelajaran Teaching Industry Berbasis Kewirausahaan dan Motivasi Belajar terhadap Peningkatan Kompetensi Keahlian Produktif Busana Butik dan Patiseri - Sutianah, Cucu (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
This study aims to examine the formulated problems; to know to what extent the implementation contribution of entrepreneurship-based teaching industry model, and students' learning motivation towards boutique and patisserie productive skill competence increase in SMK N 9 Bandung. The method adopted to address problems is quantitative approach with correlation techniques. Data collection is conducted through questionnaire dissemination and document studies. This study uses population sample. Results of correlation test and t test are as follow: implementation contribution magnitude of entrepreneurship-based teaching industry model on productive skill competence increase is in fairly high criteria, contribution magnitude of learning motivation on increase in boutique and patisserie productive skills competence has high criteria and implementation contribution magnitude of entrepreneurship-based teaching industry model and learning motivation towards productive skills competence increase has high criteria.